Amplification-free, highly sensitive electrochemical DNA-based sensor for simultaneous detection of stx1 and stx2 genes of Shiga toxin-producing E. coli (STEC). (10th February 2023) - Wasiewska, Luiza A.; Diaz, Fernando Garrido; Teixeira, Sofia Rodrigues; Burgess, Catherine M.; Duffy, Geraldine; O'Riordan, Alan
Highlights: A highly sensitive, multiplex electrochemical sensor was developed for the simultaneous detection of the stx1 and stx2 genes from STEC using silicon chips comprising interdigitated microelectrodes (IDEs). A selective, multiplex detection of stx1 and stx2 genes was confirmed using fluorescence and electrochemistry. The developed assay allowed for extremely high sensitivity with limit of detection of 100 zM (10 −19  M) for both genes. Sensor's specificity was confirmed using chromosomal DNA extracted from bacterial culture with no need for an amplification step. Abstract: Shiga toxin-producing E. coli (STEC) is a food-borne pathogen of significant public health concern, due to the severity of the illness it can cause at a low infection dose. The key targets in molecular-based assays to detect STEC are stx1 or stx2 genes, coding for the ability to produce Shiga T Toxin 1 and 2, respectively. The most commonly used molecular detection techniques, such as PCR and real-time PCR, are considerably time-consuming and there is an urgent need for a more rapid screening assay which could be used in agri-food settings. In this work, an amplification-free multiplex electrochemical sensor for the simultaneous detection of stx1 and stx2 genes was developed using a silicon-based chip comprising six interdigitated gold microelectrodes (IDE) sensors. Two probes complementary to stx1 and stx2 genes were immobilised on a single chip allowing for multiplex detection. The selectivity of the multiplex sensor was confirmed using fluorescence and electrochemistry. The developed assay conditions allowed for an improved limit of detection of three orders of magnitude compared to the previous reports achieving an amplification-free limit of detection of 100 zM (10 −19  M) for both, stx1 and stx2 genes. The developed sensor was validated using chromosomal DNA extracted from bacterial cultures containing either no virulence genes, stx1 gene only, and both stx1 and stx2 . Such multiplex sensors, if combined with on-chip DNA extraction, could revolutionise the point-of-use detection of STEC as well as other pathogens for instance on-farm or in the food industry.